Flood risk mapping of mountain rivers: A case study of the Burgay river - Timbe, Luis; Timbe, Edison (Maskana, 2012)
HEC-RAS, an one-dimensional hydraulic model, was used to simulate and map floods along a 10 km stretch of the Burgay river. Analysis of the results reveals that the model is capable of simulating the flood and inundation situation along rivers in the Andean region, notwithstanding scarcity of information. Local governments (e.g. municipalities) can use the flood hazard zoning maps for the sustainable management of alluvial plains, through the planning and implementation of structural or non-structural measures (e.g. land use planning) considering the physical conditions of the riverbanks.